Interactive Digital Lessons for Alkaline Group Elements via Articulate Storyline 3 - Hayuni Retno Widarti; Diah Triwidiastuti; Deni Ainur Rokhim (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
In chemistry subjects, one of the things studied is alkaline elemental chemistry. Learning elemental chemistry is not only memorization but requires a thought process to understand it, so learning media is needed. Articulate Storyline 3 is an intuitive program equipped with robust features for developing educational media. Its user-friendly design, similar to PowerPoint, and allows teachers to easily create engaging learning materials. The research aims to produce interactive learning media that were suitable for use in alkaline group elemental materials using articulate storyline 3. The development of this media used a define, design, develop, and disseminate (4-D) model. The learning media was validated by two experts and tested for readability with 12th-grade students. The development research results showed high feasibility, with material experts rating it at 86%, media experts at 84%, and student readability at 85%. Thus, the development of this learning media had met the high feasibility of use.